Psychotic-like experiences in the lonely predict conspiratorial beliefs and are associated with the diet during COVID-19 - Terenzi, Damiano; Muth, Anne-Katrin; Losecaat Vermeer, Annabel; Park, Soyoung Q. (Frontiers in Nutrition, 2022)
The Covid-19 pandemic has increased the occurrence of conspiracy theories. It has been suggested that a greater endorsement of these theories may be associated with psychotic-like experiences (PLEs), as well as with social isolation. In this preregistered study, we investigated whether both PLEs and measures of social isolation (e.g., loneliness) can predict conspiratorial beliefs and, if so, which of these variables can mediate the association with conspiratorial beliefs. Furthermore, based on previous studies on schizophrenia, we explored whether the diet is associated with PLEs and conspiratorial beliefs. Participants (N=142) completed online questionnaires measuring PLEs, social isolation, mental well-being, and conspiratorial beliefs. They also submitted their daily food intake for a week using a smartphone app. We found that loneliness predicted the endorsement of conspiracy theories during the Covid-19 lockdown. Strikingly, the proneness to experience subclinical psychotic symptoms played an underlying mediating role. In addition, these subclinical symptoms were associated with lower fruit, carbohydrate, and iron intakes, as well as with higher fat intake. Our results add insights into how conspiratorial beliefs can affect individuals’ mental health and relationships. Moreover, these results open the avenue for potential novel intervention strategies to optimize food intake in individuals with psychotic-like experiences.